2018
DOI: 10.1111/jns.12262
|View full text |Cite
|
Sign up to set email alerts
|

Individualized immunoglobulin therapy in chronic immune‐mediated peripheral neuropathies*

Abstract: Despite the well‐recognized importance of immunoglobulin therapy individualization during the treatment of chronic inflammatory demyelinating polyneuropathy (CIDP), the pathway to best achieve optimization is unknown. There are many pharmacokinetic and immunobiologic variables that can potentially influence the appropriateness of any individual therapy. Although identification of specific autoantibodies and their targets has only been accomplished in a minority of patients with CIDP, already the diagnostic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 64 publications
(82 reference statements)
0
24
0
Order By: Relevance
“…This guideline states that an IVIg maintenance dose of 1.0 g/kg over 1 to 2 days every 3 weeks has been shown to be efficacious, but the appropriate dose needs to be individualized (usually 0. in the next version of the EFNS/PNS guideline on treatment. 16,17,[29][30][31][32] About one-third of respondents indicated that they would start initial therapy in all CIDP patients irrespective of the severity of symptoms and the interference with daily life activities, while the EFNS/ PNS 2010 guideline recommends only to treat patients with moderate or severe disability. Although 5% to 30% of CIDP patients only needs one IVIg course (2 g/kg) to induce remission, almost one-third of the respondents indicated starting maintenance therapy after improvement on the first IVIg induction course without subsequent deterioration.…”
Section: Long-term Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…This guideline states that an IVIg maintenance dose of 1.0 g/kg over 1 to 2 days every 3 weeks has been shown to be efficacious, but the appropriate dose needs to be individualized (usually 0. in the next version of the EFNS/PNS guideline on treatment. 16,17,[29][30][31][32] About one-third of respondents indicated that they would start initial therapy in all CIDP patients irrespective of the severity of symptoms and the interference with daily life activities, while the EFNS/ PNS 2010 guideline recommends only to treat patients with moderate or severe disability. Although 5% to 30% of CIDP patients only needs one IVIg course (2 g/kg) to induce remission, almost one-third of the respondents indicated starting maintenance therapy after improvement on the first IVIg induction course without subsequent deterioration.…”
Section: Long-term Therapymentioning
confidence: 99%
“…15 Furthermore, the best approach to manage wear-off signs and withdrawal of IVIg is unclear. 16,17 Because of these challenges, we expect that both the diagnostic workup and treatment strategies for CIDP patients are highly variable.…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of the reasons for this heterogeneity between patients might help however to better individualize therapy with IVIg. 18 The safety is in line with the use of IVIg in CIDP. Regarding headaches, they were also the most frequent drug-related AEs reported in previous clinical studies.…”
Section: Discussionmentioning
confidence: 81%
“…Anti-neurofascin 155 (anti-NF155) and anti-contactin 1 (anti-CNTN1) antibodies have been identified in approximately 3–10% of patients with chronic infammatory polyneuropathies [1618]. Patients who tested positive to these paranodal antibodies responded favourably to B-cell depleting therapies like rituximab over more traditional therapeutic options like IVIg or plasmapheresis.…”
Section: Introductionmentioning
confidence: 99%
“…Many individuals with CIDP require long term maintenance treatment with IVIg to effect disease stability and studies of serum IgG levels in treatment responders have revealed that patients actually achieve a steady state wherein both pre- and post-treatment IgG levels are almost identical [23]. The implications of this are profound, as it suggests there is an individual threshold above which patients remain stable [16]. Although at the present time identifying this threshold in any given patient is a matter of trial and error, further validation of reference ranges in which disease control is achieved provides promise for a future wherein IVIg is administered with the aim to achieve pre-specified IgG levels [23].…”
Section: Introductionmentioning
confidence: 99%